1988
DOI: 10.1002/j.1551-8833.1988.tb03023.x
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum‐Fulvic Acid Interactions: Mechanisms and Applications

Abstract: The process of fulvic acid (FA) coagulation using aluminum coagulants (alum, polyaluminum chloride, and aluminum chloride) was studied in order to improve FA rehymoval during water treatment. The mechanism of FA removal is directly related to the form of aluminum in solution. Specific conditions and aluminum species that exist during the charge neutralization‐precipitation, adsorption, and simultaneous precipitation reaction mechanisms are discussed, as is the effect of calcium on FA removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
7

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 21 publications
1
46
0
7
Order By: Relevance
“…Because of electrostatic effects of DBP precursors decreasing, DBP precursors precipitated through self-aggregation and charge neutralization with aluminum species (6,8). In this study, more THM precursors were neutralized by PACl with a higher K-Al 13 content than AlCl3.…”
Section: Role Of Aluminum Speciation In Removal Of Dbp Precursors Witmentioning
confidence: 65%
“…Because of electrostatic effects of DBP precursors decreasing, DBP precursors precipitated through self-aggregation and charge neutralization with aluminum species (6,8). In this study, more THM precursors were neutralized by PACl with a higher K-Al 13 content than AlCl3.…”
Section: Role Of Aluminum Speciation In Removal Of Dbp Precursors Witmentioning
confidence: 65%
“…The flocs generated from Al 13 polymer showed a larger flocs size and a rougher surface structure than other Al species [21]. It has been suggested that adsorption onto Al hydroxide precipitates is an important pathway for the removal of NOM [34], and the extent of adsorption depends on the flocs structure and morphology, which was proved by the results of Fig. 7.…”
Section: Role Of Flocs In Ha Removalmentioning
confidence: 67%
“…On one hand, although eutrophication is menacing the safety of drinking water supply, the coagulation behavior of Al coagulants in eutrophic water has not been systemically studied. On the other hand, although the influence of Al speciation on coagulation behavior has received a lot of attention (11,24,28,29), few investigators focused on the effect of Al13 species on the coagulation efficiency in raw water. Furthermore, the relationship between Al speciation and coagulation behavior needs clarification from the viewpoint of the transformation of Al hydrolysis products during the coagulation process.…”
Section: +mentioning
confidence: 99%